2022
DOI: 10.3390/nu14194103
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Neuroprotective Effects of Extracts from Oat Seedlings against Alzheimer’s Disease

Abstract: The physiological or dietary advantages of germinated grains have been the subject of numerous discussions over the past decade. Around 23 million tons of oats are consumed globally, making up a sizeable portion of the global grain market. Oat seedlings contain more protein, beta-glucan, free amino acids, and phenolic compounds than seeds. The progressive neurodegenerative disorder of Alzheimer’s is accompanied by worsening memory and cognitive function. A key indicator of this disorder is the unusual buildup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Interestingly, no significant associations were found between iAge vs. LDL or HDL at baseline ( Supplementary Materials Figure S5 ). Previous studies on OBC have demonstrated a direct effect on LDL and cholesterol metabolism, and could thus positively influence both cardiovascular disease and neurological disorders such as Alzheimer’s Disease and Parkinson’s Disease [ 60 , 61 ]). More generally, it has been well established that oats and their constituents have a beneficial effect on various health-related mechanisms, including cholesterol maintenance, satiety, and protection from carcinogenesis in the colon [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no significant associations were found between iAge vs. LDL or HDL at baseline ( Supplementary Materials Figure S5 ). Previous studies on OBC have demonstrated a direct effect on LDL and cholesterol metabolism, and could thus positively influence both cardiovascular disease and neurological disorders such as Alzheimer’s Disease and Parkinson’s Disease [ 60 , 61 ]). More generally, it has been well established that oats and their constituents have a beneficial effect on various health-related mechanisms, including cholesterol maintenance, satiety, and protection from carcinogenesis in the colon [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, most of the studies have been carried out on animals or cells, whereas human clinical trials have been rare. Secondly, most of the saponins are derived from natural drugs, and their extraction or isolation presents some difficulties [ 246 ]. Thirdly, although natural saponins are effective, future chemical modifications and synthesizing may improve their activity and yield while reducing adverse effects [ 247 ].…”
Section: Conclusion and Perspectivementioning
confidence: 99%